Does Interpersonal Relations and Work Incentives Affect Work Motivation and Organizational Commitments? - Ramaditya, Muhammad; Liana, Lisa Rosa; Maronrong, Ridwan (Jurnal Analisis Bisnis Ekonomi, 2020)
This study aims to determine the effect of interpersonal relationships and work incentives on work motivation and organizational commitment of PT. Technology Karya Mandiri. The research sample was total all employees of 70 respondents. The method of collecting data through a questionnaire and used path analysis method using SmartPLS 3.0. Based on the results of the study, work motivation and organizational commitment has a positive and significant effect on interpersonal relationships. Work motivation and organizational commitment has a positive and significant effect on work incentives. Moreover, Organizational commitment has a positive and significant effect on work motivation. Work motivation has a negative and not significant effect on interpersonal relationships through organizational commitment. Work motivation has a negative and not significant effect on work incentives through organizational commitment. This study gives implications to provide a knowledge and optimization of human resource management strategies. The enhancement of motivation and commitment can be well received by his subordinates and other continuous efforts are made to improve both operational improvement and continuous improvement to create a highly dedicated human resources management.